Experimental supporting data on DIS3L2 over nonsense-mediated mRNA decay targets in human cells - da Costa, Paulo J. (2020)
In this article, we present supportive data related to the research article “A role for DIS3L2 over natural nonsense-mediated mRNA decay targets in human cells” [1], where interpretation of the data presented here is available. Indeed, here we analyze the impact of the DIS3L2 exoribonuclease over nonsense-mediated mRNA decay (NMD)-targets. Specifically, we present data on: a) the expression of various reporter human β-globin mRNAs, monitored by Northern blot and RT-qPCR, before and after altering DIS3L2 levels in HeLa cells, and b) the gene expression levels of deregulated transcripts generated by re-analyzing publicly available data from UPF1-depleted HeLa cells that were further cross-referenced with a dataset of transcripts upregulated in DIS3L2-depleted cells. These analyses revealed that DIS3L2 regulates the levels of a subset of NMD-targets. These data can be valuable for researchers interested in the NMD mechanism.